The geopolitical dimension of the State interest: the Western South Atlantic and its relevance for Argentina - Magnani, Ezequiel (2020)
What factors cause states to give geopolitical relevance to certain geographical areas? What isthe strategic importance that Argentina gives to the Western South Atlantic? To answer the questions, this article reviews the main geopolitical traditions in order to identify those factors that make a geographical space relevant for the interest of a determined State. Then, is conducted out a qualitative case study in order to elaborate, in the first place, a geopolitical analysis of the Western South Atlantic thought the analysis of official documents of the Ministry of Defense and the Ministry of Foreign Affairs of Argentina. Considering this, we conclude that the presence of geopolitical factors such as the economic potential of the region, the sovereignty disputes and the uncertainty regarding the continuity of the Antarctic Treaty and the Madrid Protocol as well as the possible future adverse scenarios, make the Argentinean State pay considerable attention to the Western South Atlantic region when establishing its objectives and priorities of foreign policy and national defense.